2016
DOI: 10.1007/s11356-016-6605-5
|View full text |Cite
|
Sign up to set email alerts
|

The bioaccumulation of lead in the organs of roe deer (Capreolus capreolus L.), red deer (Cervus elaphus L.), and wild boar (Sus scrofa L.) from Poland

Abstract: The aim of this study was to evaluate the level of lead (Pb) in the livers and kidneys of free-living animals from Poland, with regard to the differences in tissue Pb content between the species. The research material consisted of liver and kidney samples collected from roe deer (Capreolus capreolus), red deer (Cervus elaphus), and wild boar (Sus scrofa) that had been hunted in 16 voivodeships of Poland. The concentration of lead had been measured using inductively coupled plasma optical emission spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The exposure may be directly related to the distance of organs from the gunshot wound; the effect of this factor may be minimised by careful collection of test matrices or organs intended for human consumption [ 31 ]. This study demonstrated that the concentrations of Pb in kidneys and liver calculated for wet weight were approximately 10–15% higher than concentrations reported for the organs of roe deer, red deer and wild boars from various regions of Poland [ 2 ]. In the cited study, levels of Pb ranged from 0.45 for roe deer liver and 0.50 mg·kg −1 w.w. for wild boar liver.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The exposure may be directly related to the distance of organs from the gunshot wound; the effect of this factor may be minimised by careful collection of test matrices or organs intended for human consumption [ 31 ]. This study demonstrated that the concentrations of Pb in kidneys and liver calculated for wet weight were approximately 10–15% higher than concentrations reported for the organs of roe deer, red deer and wild boars from various regions of Poland [ 2 ]. In the cited study, levels of Pb ranged from 0.45 for roe deer liver and 0.50 mg·kg −1 w.w. for wild boar liver.…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, meat, liver and kidneys are consumed by humans, and for this reason, the presence of harmful xenobiotics in these organs can pose a real threat to human health. Considering the above, the assessment of the safety and quality of food products sourced from game is very important [ 2 , 5 , 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health authorities pay particular attention to testing food produced by animal or plant farming for metal content. A number of research papers also discussed the issue of metal content in the tissues of wild animals (Bakowska et al 2016, Dip et al 2001, Długaszek and Kopczyński 2011, Medvedev 1999, Oyaro et al 2007). Wild animals are commonly believed to be healthier, and their meat is safer for consumption, due to their “healthier,” more natural nutrition.…”
Section: Introductionmentioning
confidence: 99%